Longitudinal study of endodontic and periapical status of an adult Danish population examined in 2009, 2014, and 2019: a repeated cohort study - Ankur Razdan; Lars Schropp; Michael Væth; Lise-Lotte Kirkevang (Medical Journals Sweden, 2024)
Objective: To describe endodontic changes in an adult Danish population (C2;2009-2014-2019) and compare them with a similar cohort (C1;1997-2003-2008). Material and methods: A randomly selected cohort (C2) with three full-mouth radiographic examinations. The frequencies of teeth, apical periodontitis (AP), root filled teeth, and lost teeth in C2 were compared to a similar cohort (C1) using regression analyses; effect of age, cohort, and period was assessed. Results: C1 had 330 and C2, 170 participants (mean age, C1: 42.9; C2: 47.3 years, p < .001). The proportion of individuals with no AP was similar in C1 and C2 (p = .46). C2 had a higher proportion of individuals with no root filled teeth (p < .001) and no tooth loss (p = .02) than C1. The proportion of AP and root filled teeth increased with age in both cohorts. C2 had fewer root filled teeth and lost teeth, fewest lost teeth in the youngest age groups. Conclusions: In C2, the prevalence of teeth with AP and root fillings increased with age, and few teeth were lost. Change in proportion of AP was similar in two cohorts; fewer root filled teeth and lost teeth in C2. The proportion of lost teeth in C2 showed cohort effect for older age groups.